Flexural behaviour of reinforced concrete beams containing glass wastes as partial replacement of fine aggregate and cement - Osman, Mohamad Hairi; A.Rahman, Manisah (Penerbit UTHM, 2017)
New product development of concrete materials give advantages in terms of cost and wastage of materials. Thus, one effective way is to use disposable materials such as waste glass in concrete to minimize the use of raw materials. In the present study, the use of waste glass was conducted to determine its suitability as a material replacement in the making concrete.